AN INTEGRATED APPROACH TO SELECTING THE OPTIMAL SET OF MACHINES FOR SORTING AND CRUSHING MUNICIPAL SOLID WASTE AND SUBSTANTIATION OF THEIR KEY PARAMETERS - Khankelov, Tavbay; Sydykova , Gulnar; Radkevich, Maria; Gapirov, Abdusamin; Sabirova, Diloram; Komilov, Samandar (Journal of Applied Engineering Science, 2025)
The article is devoted to solving a complex problem, including the issues of selecting the optimal set of machines and the technological scheme for implementing the sorting and crushing of municipal solid waste at transfer and recycling stations, and the justification of the key parameters of crushing and sorting machines, considering properties of waste. When examining the main parameters, the input and output characteristics of machines are considered in the developed technological scheme. When determining the properties of waste, 12 administrative districts of the territory of Tashkent were used as objects for cluster sampling. Through an in-depth study of the process of sorting and crushing municipal solid waste, based on the developed technological scheme, the type and design of the crushing machine were determined. Based on the methods of regression analysis and mathematical statistics, a series of multifactor experiments were conducted on the main parameters of a hammer crusher. In addition, considering the properties of waste, the main parameters of the drum screen were determined, in particular, the diameter of the grid opening. The developed optimal set of machines with substantiated rational parameters will make it possible to maximally prepare the components of municipal solid waste for use in the form of secondary raw materials.